2018
DOI: 10.1111/bjd.16601
|View full text |Cite
|
Sign up to set email alerts
|

Kaposiform haemangioendothelioma: clinical features, complications and risk factors for Kasabach-Merritt phenomenon

Abstract: Most KHEs appeared before 12 months of age. KHEs are associated with various major complications, which can occur in combination and develop early in the disease process. Young age, large lesion size and mixed lesion type are important predictors of KMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
108
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(124 citation statements)
references
References 19 publications
7
108
2
7
Order By: Relevance
“…The hypoechoic depth of KHE and KHE + KMP was significantly greater than that in TA. Previous studies indicated that compared with the superficial KHE, the lesions that affected deeper tissues including muscle and bone were more likely to develop KMP . However, our studies showed that the total depth was not the most significant factor to distinguish the lesions.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The hypoechoic depth of KHE and KHE + KMP was significantly greater than that in TA. Previous studies indicated that compared with the superficial KHE, the lesions that affected deeper tissues including muscle and bone were more likely to develop KMP . However, our studies showed that the total depth was not the most significant factor to distinguish the lesions.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies indicated that compared with the superficial KHE, the lesions that affected deeper tissues including muscle and bone were more likely to develop KMP. 18 However, our studies showed that the total depth was not the most significant factor to distinguish the lesions. Furthermore, the greater hypoechoic area reflects greater aggressiveness, which may be associated with the pathological nature of vascular channels and thin-walled lymphatic vessels in KHE, and is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to vaccination, occurrence and aggravation of KHE/TA with or without KMP have also been reported in patients suffering local trauma or infection . Younger patients with a relatively large lesion are at high risk of developing KMP . It is therefore possible that vaccination at the site of KHE can trigger the activation of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…10 Younger patients with a relatively large lesion are at high risk of developing KMP. 11 It is therefore possible that vaccination at the site of KHE can trigger the activation of platelets. Nonetheless, whether the development of KMP following the vaccination is a coincidental finding, a consequence of needle trauma, or an inflammatory or immunological reaction to vaccination is unclear based on current knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we categorized KHE into three distinct morphological types: superficial, mixed and deep. Superficial lesions involve the dermis, subcutaneous tissue and deep fascia, but do not infiltrate deeply into muscle, bone and intrathoracic sites . Although many of these lesions do not lead to life‐threatening complications, some superficial KHE/TA can grow dramatically and destroy tissue, and leave irreversible skin changes.…”
Section: Discussionmentioning
confidence: 99%